TINGKAT KETERCAPAIAN DALAM PENDAMPINGAN LUKIS KALIGRAFI DENGAN MENGGUNAKAN LITHOPONE DAN BUBUK MARMER DI PESANTREN RANCA HERANG - Wawan Suryana; Ariesa Pandanwangi; Ida Ida; Belinda Sukapura Dewi; Ismet Zainal Effendi; Muhamad Ali Rahim; Basituasi Pane (LPPM Universitas Bina Bangsa, 2023)
The life skills of graduates of the Ranca Herang Islamic boarding school are important things that are considered by the management. This reason underlies that the students need to improve life skills for the future, besides that the material provided at Islamic boarding schools is focused on deepening the verses of the Al Quran. The method used is the questionnaire method and practice method dan demo method. Participants who took part in this training amounted to 29 students. This mentoring process can be said to be successful because more than 90% of the participants were able to answer questions after the mentoring properly, besides that it was proven by the works made by the participants who made good compositions, combining bright colors with soft colors. Participants are also supported by the ability to create textures on the canvas surface. So that the work looks more dynamic because the surface of the canvas looks like a relief. The importance of this ability for participants, because it can be used as a basis for developing this potential by opening new businesses that are expected to increase economic capacity in the future